2016
DOI: 10.14260/jemds/2016/821
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasound in Evaluation of Retroperitoneal Lesions

Abstract: BACKGROUNDThe retroperitoneum contains the adrenals, kidneys and ureters, the duodenal loop, pancreas, great vessels with their branches and associated lymph node chains, ascending and descending portions of the colon including the caecum, the retroperitoneal sonographic images are frequently degraded by bowel gas, thick muscles, fat, ribs, the lower lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
1
Order By: Relevance
“…USG correctly detected 46 out of the total 50 cases having an accuracy of 92% for the detection and evaluation of retroperitoneal lesions which was more than the current study [3] . Another study carried out by Harinath et al in 30 patients comparing both USG and CT in the evaluation of abdominal masses concluded that the CT was more sensitive than USG in demonstrating the morphological features of abdominal masses like echogenicity, vascularity, density, contrast enhancement characters, tumoral necrosis, calcifications, presence or absence of fat, regional lymphadenopathy, infiltration into the adjacent structures and distant metastase [8] .…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…USG correctly detected 46 out of the total 50 cases having an accuracy of 92% for the detection and evaluation of retroperitoneal lesions which was more than the current study [3] . Another study carried out by Harinath et al in 30 patients comparing both USG and CT in the evaluation of abdominal masses concluded that the CT was more sensitive than USG in demonstrating the morphological features of abdominal masses like echogenicity, vascularity, density, contrast enhancement characters, tumoral necrosis, calcifications, presence or absence of fat, regional lymphadenopathy, infiltration into the adjacent structures and distant metastase [8] .…”
Section: Discussioncontrasting
confidence: 50%
“…Advantage of USG over MDCT was that, USG is easily accessible and there is no exposure to ionizing radiations in USG as compared to MDCT [21] . However, USG is dependent on the proficiency of the operator, which could impact its diagnostic utility [3] . Nevertheless, it can be considered as a preliminary imaging tool in patients with symptoms related to retroperitoneal pathology.…”
Section: Discussionmentioning
confidence: 99%